Lateral performance of a new hybrid CFS shear wall panel for mid-rise construction. (May 2020) - Usefi, Nima; Ronagh, Hamid; Sharafi, Pezhman
ABSTRACT: Hybrid shear walls composed of cold-formed steel (CFS) open sections and square hollow sections (SHS) have recently attracted attention for lightweight midrise buildings, as a result of their relatively strong lateral load-bearing performance. A new hybrid CFS shear wall system with SHS truss skeleton is presented in this study in order to improve the lateral behaviour of lightweight steel frames, in compliance with standard codes. For this purpose, eleven full-scale experimental tests were conducted to assess the shear resistance, stiffness, ductility, and energy absorption of the proposed wall panels. The study also investigates the failure modes of the hybrid walls and suggests solutions for improving the existing structural weaknesses. The results showed that employing the SHS truss configuration for one side of the light steel walls can significantly enhance the energy absorption, compared to the traditional CFS walls. The SHS truss also has a considerable effect on decreasing the chance of chord stud buckling; i.e. load-bearing capacity. Specimens sheathed with gypsum board offer higher strength and ductility ratio with a few minor localized failures, compared to specimens without sheathing board. The results also indicate that the low strength to weight ratio of hybrid walls makes them a practical solution for mid-rise lightweight constructions. Highlights: Experimental tests are conducted for investigating the lateral performance of proposed hybrid walls. The hybrid wall provides higher shear resistance and energy absorption compared to traditional CFS walls. Proposed hybrid wall is suitable for application in mid-rise structures.